Encryption Technology for Computer Network Data Security Protection - Yu, Yang (Security and communication networks, 2022)
In order to solve the network security problem of data encryption technology, this paper proposes a research method of computer network information security maintenance based on data encryption technology. Taking the network reporting system of a mining enterprise as the research object, this paper comprehensively expounds on the design of network reporting system and data encryption in network communication from the aspects of demand investigation, demand analysis, system design, software system development, and so on and implements the development by using BS architecture + independent client. The experimental results show that the AES algorithm can be independently designated as 128 bits, 192 bits, and 256 bits. Conclusion. This scheme can realize the rapid and safe transmission of data information and provide an effective means for the transmission of confidential documents on the network, so it has a good application prospect.